Architecture of the historic center of Cuenca – Ecuador: colour study and proposals - Achig, María Cecilia (Universidad de Cuenca, 2016)
Current research main objective is to identify colours that traditionally have been use in Cuenca´s Historical Center civil architecture. To reach this objective, a methodology has been developed that includes historic data, stories and testimonies of people that have kept in their memory, the colours that have been part of the city´s image. Additionally, prospective samples or "calas” were obtained to discover in situ, colours that were hidden in the walls and other facades´ elements of some historical patrimony buildings. This enabled to make a historical colour palette, which serves as a basic instrument to be taken in account in several chromatic proposals regarding buildings and urban sections inside Cuenca´s Historic Center.Keywords: historical center of Cuenca, facades, palette, colour proposals.